2020
DOI: 10.12681/jhvms.22967
|View full text |Cite
|
Sign up to set email alerts
|

Genetic improvement of indigenous Greek sheep and goat breeds

Abstract: The objective of the study was twofold: (i) to review the genetics of production and resilience traits of indigenous Greek small ruminant breeds as well as the evolution of national breeding programs, and (ii) explore innovative and feasible approaches to overcome the challenges and constraints towards improving these breeds and enhancing the sustainability of the small ruminant sector. Previous studies on the genetic basis of production and resilience traits of indigenous breeds revealed high improvement pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 68 publications
(80 reference statements)
0
5
0
Order By: Relevance
“…Accurate pedigree information and collection of on-farm performance data of individual animals are essential for accurate genetic selection [52]. Moreover, using high breeding value rams from elite flocks ensures efficiency and speeds up the genetic improvement process [53]. Nowadays, breeding innovations are associated mainly to the advances in molecular genetics and DNA analysis, which have boosted the development of new tools in breeding programs and to the formation of selection indexes which combine productional and functional traits [54][55][56].…”
Section: Resultsmentioning
confidence: 99%
“…Accurate pedigree information and collection of on-farm performance data of individual animals are essential for accurate genetic selection [52]. Moreover, using high breeding value rams from elite flocks ensures efficiency and speeds up the genetic improvement process [53]. Nowadays, breeding innovations are associated mainly to the advances in molecular genetics and DNA analysis, which have boosted the development of new tools in breeding programs and to the formation of selection indexes which combine productional and functional traits [54][55][56].…”
Section: Resultsmentioning
confidence: 99%
“…: 22.6% of all herds; Skopelos: 2.5%; and indigenous Capra prisca: 25.6%) [24]. In general, indigenous breeds of sheep and goats are considered to be less susceptible to disease threats than many mainstream, high-production breeds [25,26], and relevant findings have also been reported regarding Greek breeds [27,28]. Moreover, indigenous breeds of sheep and goats are considered to be more tolerant to adverse weather conditions; previous studies have reported genetic differences in adaptation to temperature stress and, thus, resilience to extreme temperatures [29,30], which are mediated through a complex network of genes [31,32].…”
Section: Relevance Of Findingsmentioning
confidence: 94%
“…The predominant type of production is dairy, with over 95% of animals in the country being milked. Many reports are available, presenting morphological characteristics of sheep and goat breeds in Greece (e.g., for sheep: [1][2][3][4][5], for goats: [6,7]).…”
Section: Introductionmentioning
confidence: 99%